Evaluation of The Success of Using a SAP-Based ERP System With Theory of Planned Behavior (TPB) Model - Agnes Yemima; R. Wahjoe Witjaksono; Luthfi Ramadani (International Journal of Community Service Learning, 2024)
PT. XYZ has implemented System Application and Product in data processing (SAP) software to support business processes in the company. The success or failure of system implementation can be assessed from non-technical aspects, namely that users can accept and use the SAP system well. The aim of this research is to evaluate the use of SAP software through Theory of Planned Behavior (TPB) modeling. Attitudes, subjective norms, perceived behavioral control, behavioral intentions, and behavior are the variables used in this modeling. This TPB modeling explains the factors that influence an individual's interest and behavior in using SAP software. An individual's intention to use SAP software is influenced by attitudinal variables, perceived behavioral control, and subjective norms, while a person's influence to use SAP software is influenced by intention. This type of research is quantitative research through data collection using a questionnaire with 30 respondents coming from SAP users at PT. XYZ. Data analysis was carried out using the SmartPLS application. The results obtained are that attitudes have a positive and significant effect on behavioral intentions, behavioral intentions have a positive and significant effect on behavior, subjective norms have a positive and significant effect on behavioral intentions, and perceived behavioral control has a negative effect on behavioral intentions in using SAP software.